Direct binding of CEP85 to STIL ensures robust PLK4 activation and efficient centriole assembly - Yi Liu (Nature Portfolio, 2018)
Centriole duplication is tightly regulated in vivo, but the underlying molecular mechanisms are incompletely understood. Here the authors use high-resolution structural and imaging methods to show that CEP85 directly interacts with STIL and mediates efficient centriolar targeting of STIL, PLK4 activation and centriole assembly.